PTH-226 Prevalence of malnutrition in medical and surgical gastrointestinal outpatient clinics. (22nd June 2015) - Kamperidis, N; Katechia, K; Tesser, L; Robinson, D; Nightingale, J
Abstract : Introduction: UK NICE guidelines, state that patients attending an outpatient clinic for the first time, should be screened for malnutrition. 1 30% of inpatients are malnourished or at risk of malnutrition, 2 however the prevalence of malnutrition in outpatients, especially those with gastro-intestinal (GI) illnesses has not been assessed. Therefore, we aimed to determine the prevalence of malnutrition in the outpatient department (OPD) using body mass index (BMI) and% weight loss (%WL) and to assess the physicians'/surgeons' response malnutrition being detected. Method: The BMI and the WL were determined for every patient for a 2 week period and the results put in the notes immediately before the clinician's entry. The BMI and WL were scored as in the Malnutrition Universal Screening Tool (MUST). The demographic data, underlying disease and action taken were recorded. Data were statistically analysed using the chi-square test. Results: 605 patients (316 females) of mean age 54 years were included. 150 (25%) were new patients, 223 (37%) had previous abdominal surgery, 208 (34%) had inflammatory bowel disease, 73 (12%) had anorectal issues, 54 (9%) upper GI symptoms or conditions, 44 (7%) cancer and 33 (6%) had liver disease. 214 patients (35%) had co-morbidities: 107 (18%) cardiovascular, 91 (15%) endocrine, 45 (7%) musculoskeletal or connective tissue disorders, 38 (6%) respiratory, 21 (4%) non GI malignancies, 19 (3%) neurological and 10 (2%) psychiatric co-morbidities. 519 participants (86%) had a normal BMI and%WL. 86 (14%) had a BMI <20 kg/m² or had 5% WL. 61 (10%) were in MUST "medium risk" and 25 (4%) were in MUST "high risk" of malnutrition. 15 (60%) of the "high risk" patients were under the care or referred to a dietitian compared to 19 (28%) of "medium risk" patients. The prevalence of malnutrition was independent of sex, age, history of previous surgery and co-morbidity. There was no difference in the prevalence of malnutrition between new and follow up patients. Malnourished patients with IBD (38, 18%) vs. non-IBD (48, 12%) and patients with cancer (11, 25%) vs. non cancer (75, 13%) were more likely to be malmourished (p < 0.05). Conclusion: The risk of malnutrition in our outpatient department is 14%. IBD and cancer patients have a higher prevalence. Most patients with malnutrition (52, 61%) are not being seen by a dietitian. Disclosure of interest: None Declared. References: NICE, Quality standard for nutrition support in adults. 2012 Vera Todorovic CR, Marinos Elia, The MUST explanatory booklet. A guide to the Malnutrition Universal Screening Tool (MUST) for adults